Road to Revolution - Wulterkens, Benjamin (My University, 2009)
A person's life is shaped by the world around him. It is the purpose of this paper to show how the early events of Ernesto Guevara shaped both his views on life and actions throughout his life. He is now considered to be one of the major revolutionary leaders of our time. Yet, Che was not just created out of a vacuum. The events of his early life were the major catalyst needed to create this revolutionary. It was his two trips through South America on a motorcycle that propelled him to fight for change for the rest of his life. The economic and social plight of South America demanded change. On these trips one can see Che's political and revolutionary ideas take shape through his journals, letters, and speeches. Che became one of the major influential figures extending that change.
Keywords: Guevara, Ernesto, 1928-1967--Political and social views.; Guevara. Ernesto, 1928-1967--Travel--South America.; South America--Social conditions.; Guevara, Ernesto, 1928-1967--Correspondence.; Guevara, Ernesto, 1928-1967--Diaries.